PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK UNILEVER - Salomo Fernando; Remista Simbolon (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
Purchasing decisions are important for a company to run its business. Promotion in research becomes a variable that will be studied as a factor that influences purchasing decisions. This study aims to see the effect of promotion in influencing purchasing decisions. The data in this study were collected from Indonesian Adventist University students who filled out the questionnaires distributed and the data collected were 135 students. From the results of tests carried out with the help of SPPS 26, it was found that the results were significant for promotions in influencing purchasing decisions and gave the effect of 61.7%.